Think least of death : Spinoza on how to live and how to die - Nadler, Steven M., 1958- (Princeton, New Jersey : Princeton University Press, 2020)
The seventeenth-century Dutch-Jewish philosopher Baruch Spinoza has long been known - and vilified - for his heretical view of God and for the radical determinism he sees governing the cosmos and human freedom. Only recently, however, has he begun to be considered seriously as a moral philosopher. In his philosophical masterpiece, the Ethics, after establishing some metaphysical and epistemological foundations, he turns to the "big questions" that so often move one to reflect on, and even change, the values that inform their life: What is truly good? What is happiness? What is the relationship between being a good or virtuous person and enjoying happiness and human flourishing? The guiding thread of the book, and the source of its title, is a claim that comes late in the Ethics: "The free person thinks least of all of death, and his wisdom is a meditation not on death but on life." The life of the free person, according to Spinoza, is one of joy, not sadness. He does what is "most important" in life and is not troubled by such harmful passions as hate, greed and envy. He treats others with benevolence, justice and charity. And, with his attention focused on the rewards of goodness, he enjoys the pleasures of this world, but in moderation. Nadler makes clear that these ethical precepts are not unrelated to Spinoza's metaphysical views. Rather, as Nadler shows, Spinoza's views on how to live are intimately connected to and require an understanding of his conception of human nature and its place in the cosmos, his account of values, and his conception of human happiness and flourishing. Written in an engaging style this book makes Spinoza's often forbiddingly technical philosophy accessible to contemporary readers interested in knowing more about Spinoza's views on morality, and who may even be looking to this famous "atheist", who so scandalized his early modern contemporaries, as a guide to the right way of living today.
"A new way of life" -- A model of human nature -- The free person -- Virtue and happiness -- From pride to self-esteem -- Fortitude -- Honesty -- Benevolence and friendship -- Suicide -- Death -- The right way of living.
Includes bibliographical references and index.
Keywords: Spinoza, Benedictus de, -- 1632-1677.; Ethics